Development of a Physical Motor Learning Model to Improve Basic Locomotor Movement Literacy in Early Children - Putri, Mu’alfani Arsana; Hidayah, Nur; Pramono, Pramono (Cakrawala: Jurnal Pendidikan, 2022)
The research aimed to develop a learning model for physical movement (physical motor) in the form of a Daily Learning Implementation Plan (RPPH) for basic locomotor movement literacy in children aged 5-6 years. The research methodology used is research and development using the ADDIE model. The subjects for the limited-scale test were 5 students from group B2 at TK Muslimat NU 01 Bululawang, while the subjects for the large-scale test were 10 students from group B1 at TK Muslimat NU 01 Bululawang. The results showed that the overall product feasibility test average was 94.51%. This means that the developed learning model can be declared useful (valid) as a guide for teachers in learning body movements, especially basic locomotor movement literacy in early childhood.